Recurrent Out-of-Hospital Sudden Cardiac Arrest: Prevalence and Clinical Factors. (16th November 2022) - Held, Elizabeth P.; Reinier, Kyndaron; Chugh, Harpriya; Uy-Evanado, Audrey; Jui, Jonathan; Chugh, Sumeet S.
Abstract : Background: Despite improvements in management following survival from sudden cardiac arrest (SCA) and wide availability of implantable cardioverter defibrillators for secondary prevention, a subgroup of individuals will suffer multiple distinct episodes of SCA. The objective of this study was to characterize and evaluate the burden of recurrent out-of-hospital SCA among survivors of SCA in a single large US community. Methods: SCA cases were prospectively ascertained in the Oregon Sudden Unexpected Death Study. Individuals that experienced recurrent SCA were identified both prospectively and retrospectively. Results: We ascertained 6649 individuals with SCA (2002–2020) and 924 (14%) survived to hospital discharge. Of these, 88 survivors (10%) experienced recurrent SCA. Of the nonsurvivors (n=5725), 35 had suffered a recurrent SCA. Of the total 123 SCA cases with recurrent SCA, >60% occurred at least 1 year after the initial SCA (median 23 months, range: 6 days to 31 years). SCA occurred despite a secondary prevention implantable cardioverter defibrillator in 22% (n=26). Prevalence of coronary disease (36% versus 25%), hypertension (69% versus 43%), diabetes (44% versus 21%), and chronic kidney disease (35% versus 14%) was significantly higher in recurrent SCA versus single SCA survivors (n=80, P =0.01). Among individuals with no secondary prevention implantable cardioverter defibrillators before recurrent SCA, the majority had apparently reversible etiologies identified at initial SCA, with one-quarter undergoing coronary revascularization and over half diagnosed with noncoronary cardiac etiologies. Conclusions: At least 10% of SCA survivors had recurrent SCA, and a large subgroup suffered their repeat SCA despite treatment for an apparently reversible etiology. A renewed focus on careful assessment of cardiac substrate as well as management of coronary disease, hypertension, diabetes, and chronic kidney disease in SCA survivors could reduce recurrent SCA.